"The Gods Must Be Crazy": Students' Attitudes and Dispositions as Enablers and Blockers to Internationalization. (February 2022) - Ehrhardt, David; Archambault, Caroline
This article argues that students' attitudes and dispositions can be important enablers or blockers to effective internationalization of the curriculum in higher education. Using a case study of teaching African studies at a Dutch Liberal Arts and Sciences college, this article shows that students have mixed explicit attitudes toward the subject matter, but more consistent implicit dispositions that influence their understanding. Specifically, our students show strong dispositions toward agency, rationality, separation, and similarity, which clarifies some aspects of the course content but obscures others. As such, they function as both enablers and blockers to intercultural learning. Since dispositions are common among university students and relevant to a wide array of intercultural learning contexts, this study offers important insights for designing and implementing effective internationalization—in particular, the need to tailor our efforts to the specific constellation of attitudes and dispositions, the course content, and the skills of both teachers and students.